The parental leave benefit: A key family policy measure, one decade later - Mathias Huebener; Kai-Uwe Müller; C. Katharina Spieß; Katharina Wrohlich (DIW Economic Bulletin, 2016)
On January 1, 2017, the parental leave benefit will be celebrating its tenth anniversary. Although its implementation was fervidly debated, it has become a widely accepted family policy measure. Its impact on parental labor supply, the division oflabor between parents, fertility, and indicators that reflect the well-being of parents and children have been examined from a variety of perspectives. A global evaluation of relevant economic studies shows that on average, when young familiesreceive the parental leave benefit as an earnings replacement benefit, their economic stability in the first year after childbirth increases. As a result of the parental leave benefit, the employment rate of mothers decreased in the first year after childbirth, while it increased in the second year. The share of fathers who take parental leave has clearly increased, while the effects on the division of labor within the family are inconclusive. Some evidence suggests that the parental leave benefit can even have an effect on fertility. Little is known about its impact on child development. Overall, although the parental leave benefit family policy measure has been successful in many areas, its targeted effects could be augmented by additional family policy reforms.
Keywords: J12; J13; J16; J18; J21; J22; J24; 330; parental leave; parental leave benefit; family policy